2005
DOI: 10.1021/ie040157q
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Fouling Effects in LDPE Tubular Polymerization Reactors. 1. Fouling Thickness Determination

Abstract: Fouling in a low-density polyethylene (LDPE) tubular polymerization reactor is caused by the polyethylene/ethylene mixture forming two phases inside the reactor. Some of the polymer-rich phase is deposited on the reactor's inside wall, which considerably reduces heat-transfer rates. At a given reactor pressure, the reactor inside wall temperature is the critical parameter in determining when fouling occurs and this is controlled by the coolant stream temperatures. In this work, plant data and a heat-transfer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 2 publications
2
45
0
1
Order By: Relevance
“…Even for particles in the micrometer-size range, the sticking probability was limited by hydrodynamic conditions that are similar to or less severe than those encountered in industrial heat exchangers. Buchelli et al (2005) analyzed particulate fouling in a continuous LDPE polymerization reactor and found that the foulant thickness grew linearly with time. Based on the heat and mass transfer analogy and analysis of the plant data they suggested that only a small fraction of the polymer that is precipitated near the reactor wall gets attached to the wall to produce fouling.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even for particles in the micrometer-size range, the sticking probability was limited by hydrodynamic conditions that are similar to or less severe than those encountered in industrial heat exchangers. Buchelli et al (2005) analyzed particulate fouling in a continuous LDPE polymerization reactor and found that the foulant thickness grew linearly with time. Based on the heat and mass transfer analogy and analysis of the plant data they suggested that only a small fraction of the polymer that is precipitated near the reactor wall gets attached to the wall to produce fouling.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a study of fouling in a low-density polyethylene tubular polymerization reactor, Buchelli et al [21] found that the fouling was driven by phase separation and the foulant thickness grew linearly with time.…”
Section: Deposit Thicknessmentioning
confidence: 99%
“…Moreover, they were frequently extrapolated strongly to high process temperatures and pressures and ideal mixing laws have been applied without question [6,9,10,17]. This means density, heat capacity, viscosity and heat conductivity have to be described approximately between 1500 and 3500 bar and 100 to 300°C.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Calculating the ethene heat capacity can be done using one of the three empirical correlations listed in Tab [6,9,10,17]. This is a reasonable first approach due to the relative similar chemical nature of polymer and solvent.…”
Section: Heat Capacitymentioning
confidence: 99%